A competition between stress triaxiality and joule heating on microstructure evolution and degradation of SnAgCu solder joints. (June 2020) - Siswanto, Waluyo Adi; Arun, M.; Krasnopevtseva, Irina V.; Surendar, A.; Maseleno, Andino
Abstract: In this study, the simultaneous role of thermal cycling and electric current on the microstructure and degradation behavior of solder joints was investigated. For this purpose, FEM simulations and experimental works were performed on IGBT modules with the diverse solder joint thicknesses of 50, 70 and 90 μm. The results showed that the thermal cycling effect is a dominant factor in degradation of solder joints in thin solder layer (50 μm) which is due to the intensified stress triaxiality and higher accumulated creep energy per volume of the solder layer. However, in thicker solder joints (90 μm), the joule heating effect of electric current comes into play and accompanies with the thermal cycling effect to degrade the solder joint. This event is due to the fact that the thicker layer has a higher resistance to the electric current and induces more accumulated energy. This phenomenon is inconsistent with the thermal cycling effect which has an inverse relation with the solder thickness. Finally, it was revealed that an optimum solder thickness (70 μm) includes the minimum accumulated energy from simultaneous effects of thermal cycling and joule heating.